Influence of Trash-Barriering on Operation of Pumping Station with Wet-Pits. (8th April 2014) - Qiu, Baoyun; He, Shuquan; Chu, Shiji; Feng, Xiaoli
Abstract : Trash racks are set before inlet sumps of a pumping station with wet-pits in order to block trash. The flow fields before and behind the trash rack were numerically simulated and flow fields in the inlet sump were calculated using the simulated velocity distribution of the section behind the trash rack as the inlet boundary condition. Local head loss of trash-barriering increases with the increase of blockage ratio of the trash rack. When waterweeds block upper part of the trash rack, flow pattern behind the trash rack will be extremely turbulent, flow velocity of lower part of inlet section of inlet sump will increase, flow velocity of the upper part will decrease, and even backflow appears, which will deteriorate the flow pattern and increase head loss in the inlet sump. Trash-barriering has little effect on velocity distribution of impeller inlet section. Trash-barriering will not only increase head and power of the pump but also decrease the flow. For the example of the pumping station: when blockage ratios of the trash racks are 0.3, 0.5, and 0.7, operating cost will increase by 13% 43% than that of without trash racks. Therefore, the trash rack should be cleaned up timely.